Estudo do aproveitamento da fuligem da queima do bagaço da cana de açúcar em compostos de borracha (solados e placas compactas) - Diniz, Rodrigo Bertelli (2009)
The soot from burning of the bagasse of sugar cane has made environmental issues very negative, and cause serious damage to human health, such as lung problems. In an attempt to minimize this damage, studies with soot are being made so that it can be reused in the best possible way. The objective of this work was the development of compounds dark low cost, using it for the soot of sugar cane bagasse. For this goal was reached, the soot came through heat treatment with subsequent reduction of its size, the soot after treatment was used as inert load, with the polymer SBR 1502 (styrene butadiene rubber). The soot was obtained by the burning of sugar cane bagasse in boilers, soot provided by this plant Caeté (Delta / MG). Comparative compounds were developed with the variable to load inert (kaolin common, pink kaolin, calcium carbonate and soot of bagasse). The physicalmechanical properties (density, hardness, abrasion) were compared between loads, after pressing the rubber compound. For better understanding of the constituents of the soot, tests were made, among them we can mention a few techniques: thermal analysis (thermogravimetry and differential thermogravimetry), the absorption of infrared spectroscopy, textural properties (measurement of surface area), x-ray diffraction The results identified that the compound with the best result was that with the soot, due to better resistance to abrasion (mm3), density (g/cm3) and hardness (Shore A). Key-words: sugar cane; soot; rubber.